HUBUNGAN KECERDASAN INTELEKTUAL DAN KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR SISWA SD MUHAMMADIYAH 29 SUNGGAL DELI SERDANG - amaliyah amaliyah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
ABSTRACT The purpose of this study: 1). To determine the relationship of the intellectual and academic achievement of students in SD Muhammadiyah 29 Sunggal Deli Serdang. 2). To determine the relationship of emotional intelligence and student achievement in SD Muhammadiyah 29 Sunggal Deli Serdang. 3). To determine the relationship between intellectual intelligence and emotional intelligence with student achievement in SD Muhammadiyah 29 Sunggal Deli Serdang.This research is using quantitative research with 65 respondents. Data management hypothesis testing using product moment analysis, F test, t test, chi square, determination, simple regression and multiple regression.            The results showed that there is a relationship intellectual intelligence with student achievement, has a correlation value of0.787 while correlation table at 0.478, coefficient of 0.9493 F test, t test for 10.133and the determination coefficient of 0.765 (76.5%), there is a relationship of emotional intelligence and academic achievement.has a correlation value of 0.788 while correlation table at 0.476, F test coefficient of 0.673, t test of 10.155 while the t test table by 2.66 and the coefficient of determination coefficient of 0.773 (77.3%), there is a relationship emosioanal intellect and intelligence together with academic achievement.has a correlation value of 0.789 while correlation table at 0.476, coefficient of 0.9476 F test, t test of 10.211 while the t test table by 2.66 and the determination coefficient of 0.769 (76.9%) with 23.1% influenced by other factors or variables and are not examined in this study.            Based on the calculation results obtained from this study can be said that there is a significant relationship anatar intellectual intelligence and emotional intelligence to student achievement either simultaneously or in every variable. Key words: Intelligence intellectual, emotional intelligence, learning achievement